2002
DOI: 10.1108/09590550210423654
|View full text |Cite
|
Sign up to set email alerts
|

A consumer model for channel switching behavior

Abstract: With the phenomenal growth of direct order marketing with the Internet and catalogs as alternative channels, customers increasingly face more choices of where to purchase goods and services. This paper develops a formal consumer model to explain channel switching behavior. Becker’s theory of time allocation is expanded to consumer decision making between distribution channels. The final model suggests that consumers face a tradeoff when deciding where to buy goods and services. From this tradeoff an indifferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 31 publications
0
50
0
Order By: Relevance
“…Risk factors, such as transaction security and lack of privacy, lead to consumers' uncertainty. Consumers' risk perceptions significantly influence decisions about whether to purchase online or in a physical store (Burke 2002;Gupta et al 2004;Reardon and McCorkle 2002;Szymanski and Hise 2000). Thus, the following hypotheses are proposed:…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors, such as transaction security and lack of privacy, lead to consumers' uncertainty. Consumers' risk perceptions significantly influence decisions about whether to purchase online or in a physical store (Burke 2002;Gupta et al 2004;Reardon and McCorkle 2002;Szymanski and Hise 2000). Thus, the following hypotheses are proposed:…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
“…Based on the literature (Hardy 1982;Jepsen 2007;Kollmann et al 2012;Moon 2004;Noble et al 2005;Park and Kim 2003;Reardon and McCorkle 2002;Verhoef et al 2007), this study identifies six main consumer-perceived channel characteristics and classifies these characteristics into four types: perceived search benefits, Understanding multi-channel research shoppers: an analysis… perceived search costs, perceived purchase benefits, and perceived purchase costs. Table 1 shows the channel characteristics and respective types.…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
“…Some researchers have approached multi-channel e-commerce research from the perspective of buyer behaviour (Balabanis et al 2001;Kaufman-Scarborough et al 2002;Reardon et al 2002), while others have focused on Internet strategy (Porter 2001;Simons et al 2002). Based on this research we identified a number of success factors that we expected to be significant in our exemplar organisation.…”
Section: Literature Reviewmentioning
confidence: 98%
“…(Kaufman-Scarborough et al 2002;Porter 2001;Reardon et al 2002;Schoenbachler et al 2002;Simons et al 2002;Steinfield et al 2002). It implies ease of movement across channels.…”
Section: Sf2: Channel Synergymentioning
confidence: 99%
“…So that through it, timely purchase request, selective calling information, saving time and increasing comfort is possible (Reardon, 2002).…”
Section: ) Direct Marketingmentioning
confidence: 99%